Prolonged Relief of Chronic Pain from Local Anaesthetic Blocks - Ellen N Thompson (Pain Research and Management)
In a fascinating essay on the future of local anesthetic agents, Wall (1) cited a 1990 paper from the Karolinska Institute in Stockholm, Sweden, entitled 'Prolonged relief of neuralgia after regional anesthetic blocks: A call for further experimental and systematic clinical studies' (2). The Swedish researchers had found that two-thirds of 38 patients with neuralgia experienced prolonged (up to six days) relief of pain after blocking of the injured nerve.